US state-level capacity expansion pathways with improved modeling of the power sector dynamics within a multisector model. (November 2021) - Ou, Yang; Binsted, Matthew; Iyer, Gokul; Patel, Pralit; Wise, Marshall
Abstract: A key challenge for long-term power sector planning models is to simultaneously represent multisector interactions within the energy system in response to broader technological and societal factors, while considering sufficient structural details within the power sector. We incorporate improved representations of capacity markets, economic retirements, and power-plant age structure along with up-to-date technology assumptions into the power sector component of a well-established multisector model with state-level details in the US. Using the improved model, we explore US power sector scenarios that vary across assumptions about technological change and societal transitions toward a low-carbon economy. Under a combination of rapid technological change and a societal transition, capacity investments in renewable technologies triple compared to a Reference scenario, whereas investments in fossil capacity (coal, gas, and refined liquids) substantially reduce across all states in the U.S. Increased solar investments serve peak demands, while shifts from coal to gas and wind serve baseload demand. Finally, inter-state electricity trade for both net exporters and net importers also increases. Highlights: We improved power sector modeling in an integrated human-Earth system model. Four US capacity expansion scenarios are examined out to 2050 across all states. Societal low-carbon transitions entail higher electrification in all end-use sectors. Low renewable cost and low-carbon transition promote renewable capacity investment.